Increased expression of OPN contributes to idiopathic pulmonary fibrosis and indicates a poor prognosis - Jie Ji; Shudan Zheng; Yuxin Liu; Tian Xie; Xiaoyu Zhu; Yang Nie; Yi Shen; Xiaodong Han (Journal of Translational Medicine, 2023)
Abstract Background Idiopathic pulmonary fibrosis (IPF) is fibrotic lung disease with no effective treatment. It is characterized by destruction of alveolar structure and pulmonary interstitial fibrosis, leading to dyspnea and even asphyxia death of patients. Epithelial-mesenchymal transition (EMT) is considered to be a driving factor in the pathogenesis of IPF. Osteopontin (OPN) is a secreted protein widely present in the extracellular matrix and involved in the occurrence and development of a variety of diseases. Methods The original datasets were obtained from NCBI GEO databases analyzed with the online tool GEO2R and EasyGEO. Bleomycin induced mouse pulmonary fibrosis model and OPN/OPN-biotin treated mouse model were established to investigate the role of OPN in mouse pulmonary fibrosis and the target cells of OPN. A549 cells and HBE cells were used to explore the mechanism of OPN-induced epithelial-mesenchymal transition (EMT) in epithelial cells and mass spectrometry was used to detect OPN downstream receptors. Precision-cut lung slices and lentivirus-treated mice with pulmonary fibrosis were used to examine the therapeutic effect of OPN and its downstream pathways on pulmonary fibrosis. Results We demonstrate that the content of OPN in IPF bronchoalveolar lavage fluid (BALF) is high compared to the normal groups, and its expression level is correlated with prognosis. At the animal level, OPN was highly expressed at all stages of pulmonary fibrosis in mice, and the bronchoalveolar lavage fluid (BALF) could accurately reflect its expression in the lung. Next, we reveal that OPN was mainly expressed by macrophages and the main target cells of OPN were epithelial cells. Mice developed pulmonary fibrosis accompanied after treating the mice with OPN. Both in vitro and in vivo experiments confirmed that OPN could induce EMT of alveolar epithelial cells. Mechanistically, OPN binding triggered phosphorylation of FAK by CD44, thus activating snail1-mediated profibrotic protein synthesis. Inhibition of FAK phosphorylation and its downstream pathways can effectively alleviate pulmonary fibrosis in precision sections of lung tissue (PCLS) assay. OPN knockdown in bleomycin-induced lung fibrosis mice led to significantly less fibrosis. Conclusion Our data suggest that OPN mediates lung fibrosis through EMT, implicating its potential therapeutic target and prognostic indicator role for IPF. OPN may be a target for the diagnosis and treatment of IPF.